The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1097/01.ju.0000135890.08541.02
|View full text |Cite
|
Sign up to set email alerts
|

Voiding Frequency in a Sample of Asymptomatic American Men

Abstract: This study suggests that the threshold of 8 to define abnormal urinary frequency may not be correct since more than a third of our sample of asymptomatic men voided more than 8 times daily. It is probably inadvisable to apply a single set of normative values to all American men because of significant variability in regional climates and populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 15 publications
3
30
0
Order By: Relevance
“…Our study affirmed previous reports that voiding frequency increases with increasing age 6 and increasing V 24 7,14 -16 and that Vol/Void decreases with increasing age 4,6,11 and increases with increasing V 24 . 7,8,[14][15][16] These relationships suggest that, when comparing a patient's F 24 or Vol/Void measurement with an expected reference value, the expected reference value should be adjusted for the patient's age and V 24 .…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Our study affirmed previous reports that voiding frequency increases with increasing age 6 and increasing V 24 7,14 -16 and that Vol/Void decreases with increasing age 4,6,11 and increases with increasing V 24 . 7,8,[14][15][16] These relationships suggest that, when comparing a patient's F 24 or Vol/Void measurement with an expected reference value, the expected reference value should be adjusted for the patient's age and V 24 .…”
Section: Discussionsupporting
confidence: 95%
“…Our findings, supported by several others, indicate that age 4,6,11 and V 24 6,7,14-16 have significant effects on Vol/Void and F 24 measurements from asymptomatic persons. Therefore, when comparing a patient's bladder diary measurement to an asymptomatic reference population, the reference values should be adjusted for the known effects of age and V 24 within the reference population.…”
Section: Clinical Considerationssupporting
confidence: 92%
See 1 more Smart Citation
“…Men were found to have higher total fluid intakes and mean VVs than women, whereas women voided more frequently than men, and therefore, had more voids per litre of fluid intake. Moreover, Latini et al 17 found that urinary frequency was related to fluid intake in asymptomatic men. This finding demonstrates that elderly women with LUTS have lower functional bladder capacities.…”
Section: Discussionmentioning
confidence: 99%
“…Without controlling for at least some of these factors, defi ning normal urinary frequency may not be very meaningful. However, a variety of investigators have attempted to analyze urinary frequency in asymptomatic individuals [25][26][27][28][29]. A cutoff point of eight voids per 24-hour period has often been used to defi ne abnormal frequency, but these studies would suggest that one third to one half of asymptomatic individuals void nine or more times daily.…”
Section: Frequencymentioning
confidence: 99%